A Multi-Omics Approach to Evaluate the Quality of Milk Whey Used in Ricotta Cheese Production - Sattin, Eleonora; Andreani, Nadia A.; Carraro, Lisa; Lucchini, Rosaria; Fasolato, Luca; Telatin, Andrea; Balzan, Stefania; Novelli, Enrico; Simionati, Barbara; Cardazzo, Barbara (Frontiers in Microbiology, 2016)
In the past, milk whey was only a by-product of cheese production, but currently, it has a high commercial value for use in the food industries. However, the regulation of whey management (i.e., storage and hygienic properties) has not been updated, and as a consequence, its microbiological quality is very challenging for food safety. The Next Generation Sequencing (NGS) technique was applied to several whey samples used for Ricotta production to evaluate the microbial community composition in depth using both RNA and DNA as templates for NGS library construction. Whey samples demonstrating a high microbial and aerobic spore load contained mostly Firmicutes; although variable, some samples contained a relevant amount of Gammaproteobacteria. Several lots of whey acquired as raw material for Ricotta production presented defective organoleptic properties. To define the volatile compounds in normal and defective whey samples, a headspace gas chromatography/mass spectrometry (GC/MS) analysis was conducted. The statistical analysis demonstrated that different microbial communities resulted from DNA or cDNA library sequencing, and distinguishable microbiota composed the communities contained in the organoleptic-defective whey samples.